After Effects and Photoshop : - Foster, Jeff (John Wiley, 2006)
In this second edition to his bestselling book, TV and movie graphics veteran Jeff Foster provides all-new information on After Effects 7 and Photoshop CS2—plus expanded coverage of blue/green screening and titling, beautiful new images, and innovative real-world solutions for today's professionals. Better than ever, this must-have reference is still the only guide that shows how to use these two superpower programs together to achieve professional results.